2020
DOI: 10.1038/s41598-020-78174-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the papillary renal cell carcinoma subtype on oncological outcomes

Abstract: The study aimed to compare the clinicopathological features and prognosis between type I and type II papillary renal cell carcinoma (PRCC) and to investigate whether the subtypes of PRCC would affect oncological outcomes. A total of 102 patients with PRCC were recruited, of which 42 were type I PRCC and 60 type II. The clinicopathological features and oncologic outcomes of the patients were evaluated. The type II cases had a higher WHO/ISUP grading (P < 0.001), T (P = 0.003), N (P = 0.010) stage and stage g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…As reported, PRCC accounted for approximately 10%–14% of RCC in Western population. However, the incidence of PRCC was reported to be approximately 5.2%–5.6% in Japanese and Korean populations and 1.9–7.5% in Chinese population ( 5 , 16 , 17 ). In this study, PRCC accounted for 4.3% of RCC, which was significantly lower than the incidence reported in the West, but a similar incidence was reported in Japan, Korea, and China.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, PRCC accounted for approximately 10%–14% of RCC in Western population. However, the incidence of PRCC was reported to be approximately 5.2%–5.6% in Japanese and Korean populations and 1.9–7.5% in Chinese population ( 5 , 16 , 17 ). In this study, PRCC accounted for 4.3% of RCC, which was significantly lower than the incidence reported in the West, but a similar incidence was reported in Japan, Korea, and China.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of included studies are presented in Table 1 (3,(6)(7)(8)(9)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). All included studies were in retrospective designs and were published between 2001 and 2020, and the patients were recruited ranged from 1970 to 2018.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Compared with type 1 PRCC, type 2 is more often associated with a greater stage, higher Fuhrman grade, higher frequency of necrosis and sarcomatoid features with worse outcome and more aggressive disease ( 18 , 26 ). However, previous studies indicated that WHO/ISUP grade and tumor size were associated with the prognosis, rather than histologic subtype ( 24 , 27 ). Based on preoperative imaging, this case was classified as Bosniak category IV and considered malignant.…”
Section: Discussionmentioning
confidence: 90%